Electrospinning With Lyophilized Platelet-Rich Fibrin Has the Potential to Enhance the Proliferation and Osteogenesis of MC3T3-E1 Cells - Nie, Jing; Zhang, Shumei; Wu, Peng; Liu, Yuangang; Su, Yanjun (Frontiers in Bioengineering and Biotechnology, 2020)
Platelet-rich fibrin (PRF) as a reservoir of various growth factors plays an essential role in wound healing and tissue engineering at present. Electrospinning technology is an efficient approach to acquire artificial scaffold which has good biocompatibility. The goal of this study was to investigate the potential of electrospinning on the proliferation and osteogenesis of osteogenic precursor cells in vitro, with lyophilized PRF added as a component for electrospinning preparation. The surface structure of lyophilized PRF and electrospinning were investigated, and the proliferation, osteogenesis of MEC3T3-E1 cells with lyophilized PRF or electrospinning extract medium were studied. The results showed that the diameters of the lyophilized PRF pores were 1.51±0.75 μm, and lyophilized PRF medium promoted the proliferation and osteocalcin (OCN) and osteopontin (OPN) genes expression of MEC3T3-E1 cells. Furthermore, the diameters of the polyvinyl alcohol/sodium alginate/lyophilized PRF (PVA/SA/PRF) fibers were 201.14±40.14 nm. Compared to PVA/SA electrospinning extract medium and control medium, PVA/SA/PRF electrospinning extract medium also enhanced the proliferation and mineralization activity of MEC3T3-E1 cells. These results might be instructive to future clinical therapeutics with PVA/SA/PRF electrospinning for bone tissue engineering or other application.